2009
DOI: 10.1177/039463200902200208
|View full text |Cite
|
Sign up to set email alerts
|

Inflammasomes are Differentially Expressed in Cardiovascular and other Tissues

Abstract: To determine the expression of components in Toll-like receptors (TLRs)/Nod-like receptors (NLRs)/ infiammasome/caspase-llinterleukin (IL-l)-P pathway, we examined the expression profiles of those genes by analyzing the data from expression sequence tag cDNA cloning and sequencing. We made several important findings: firstly, among 11 tissues examined, vascular tissues and heart express fewer types of TLRs and NLRs than immune and defense tissues including blood, lymph nodes, thymus and trachea; secondly, brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
174
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 162 publications
(184 citation statements)
references
References 37 publications
6
174
1
3
Order By: Relevance
“…In order to generate valid confidence intervals, sample sizes have to be estimated with statistical tools of sample size determination (Rosner, 2000) as we reported ; 5) Verifiable methods: Experimental methods are available to verify the data generated by the database mining ; and 6) A new working model/hypothesis: Through database mining, a new knowledge gap will be identified, and a new hypothesis will be proposed to test fewer, much more-focused genes in further experiments. The following sections will illustrate these principles in our own publications (Chen et al, 2010;Jan et al, 2010;Ng et al, 2004;Virtue, 2011;Yang et al, 2006a;Yang et al, 2006b;Yin et al, 2009). In our invited review, we pointed out that the identification and molecular characterization of self-antigens expressed by human malignancies, that are capable of elicitation of anti-tumor immune responses in patients, have been an active field in tumor immunology .…”
Section: Principles Of Database Miningmentioning
confidence: 97%
See 4 more Smart Citations
“…In order to generate valid confidence intervals, sample sizes have to be estimated with statistical tools of sample size determination (Rosner, 2000) as we reported ; 5) Verifiable methods: Experimental methods are available to verify the data generated by the database mining ; and 6) A new working model/hypothesis: Through database mining, a new knowledge gap will be identified, and a new hypothesis will be proposed to test fewer, much more-focused genes in further experiments. The following sections will illustrate these principles in our own publications (Chen et al, 2010;Jan et al, 2010;Ng et al, 2004;Virtue, 2011;Yang et al, 2006a;Yang et al, 2006b;Yin et al, 2009). In our invited review, we pointed out that the identification and molecular characterization of self-antigens expressed by human malignancies, that are capable of elicitation of anti-tumor immune responses in patients, have been an active field in tumor immunology .…”
Section: Principles Of Database Miningmentioning
confidence: 97%
“…For example, our own research will examine mRNA transcript expressions of about 30 genes including all the reported toll-like receptors, NOD-like receptors, and inflammatory caspases in more than ten tissues. This scope allows us to obtain a panoramic view on the expressions of inflammatory pathways without focusing on a single gene in many tissues (Yin et al, 2009); 3) Suitable databases: Databases that are suitable for examining the hypothesis are available for online analytic search, which is also similar to the methods and reagents for experimental projects; 4) Sizable experimentally verified data for generating confidence intervals with statistical significance: To consolidate the results generated from database mining, the experimentally verified data are published by various laboratories, which can be used to generate statistically significant confidence intervals by using the same online analysis tools as we reported (Virtue, 2011). In this study, our analysis in the TargetScan yielded 524 microRNAs, which were predicted to participate in 1368 unique interactions with the 33 inflammatory gene mRNAs.…”
Section: Principles Of Database Miningmentioning
confidence: 99%
See 3 more Smart Citations